Earthen architecture : past, present and future, proceedings of the International Conference on Vernacular Heritage, Sustainability and Earthen Architecture, Valencia, Spain, 11-13 September 2014 - Mileto, Camilla; Vegas, Fernando; García Soriano, L.; Cristini, Valentina (Balkema Book, 2015)
Earthen architecture is widespread all over the world and demonstrates a significant richness of varieties both in application and in materials used. This book discusses and debates the lessons that can be learned from earthen architecture to create sustainable architecture today, both for the conservation of traditional existing buildings and the design and construction of new ones. It deals with the study of earthen architecture around the world in order to preserve our earthen built heritage and proposes these building techniques as a sustainable option for building a new architecture of th.